Developing Biology Teacher Candidates’ Skills in Constructing Multiple-Choice Items through Peer Tutoring: A Qualitative Item Analysis - Wijarini, Fitri; Ilma, Silfia; Nofiana, Mufida; Puspita, Laila (Biosfer: Jurnal Tadris Biologi, 2026)
The ability to construct high-quality multiple-choice items is an essential component of assessment literacy for prospective teachers. However, novice item writers often face difficulties in maintaining structural consistency and cognitive alignment. This qualitative descriptive study examines the role of peer tutoring in developing biology teacher candidates’ skills in constructing multiple-choice items. The participants were 36 undergraduate students enrolled in an Evaluation of Learning Outcomes course, selected through purposive sampling and grouped into six peer tutoring teams. Data were collected through document analysis of 60 items produced before and after peer tutoring, classroom observations, and semi-structured interviews. Analysis was conducted using ten qualitative indicators covering content validity, cognitive alignment, and technical quality. The results show consistent improvement across all indicators, with an average increase of 25.30%, particularly in option length comparability (35%), stem clarity (32%), option homogeneity (30%), and cognitive alignment (29%). Pengembangan Keterampilan Calon Guru Biologi dalam Menyusun Soal Pilihan Ganda melalui Bimbingan Sejawat: Analisis Soal Kualitatif ABSTRAK: Kemampuan menyusun soal pilihan ganda yang berkualitas merupakan bagian penting dari literasi asesmen calon guru. Namun, penulis soal pemula sering mengalami kesulitan dalam menjaga konsistensi struktur dan kesesuaian tingkat kognitif. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk mengkaji peran bimbingan sejawat dalam mengembangkan keterampilan calon guru biologi dalam menyusun soal pilihan ganda. Partisipan penelitian adalah 36 mahasiswa yang mengikuti mata kuliah Evaluasi Hasil dan Proses Pembelajaran, dipilih melalui purposive sampling dan dibagi ke dalam enam kelompok bimbingan sejawat. Data dikumpulkan melalui analisis dokumen terhadap 60 butir soal sebelum dan sesudah bimbingan sejawat, observasi, serta wawancara semi-terstruktur. Analisis menggunakan sepuluh indikator kualitatif. Hasil menunjukkan peningkatan pada seluruh indikator dengan rata-rata 25,30%, terutama pada kesetaraan panjang opsi (35%), kejelasan pokok soal (32%), homogenitas opsi (30%), dan kesesuaian kognitif (29%).